ANALISIS KUALITAS PAVING BLOCK HASIL HOME INDUSTRY DI KABUPATEN KUBU RAYA - Febrian, M. Noval; Irvhaneil; Syahwanti, Hezliana (Fakultas Teknik Universitas Panca Bhakti, 2025)
Paving blocks are construction materials widely used in infrastructure development because they are easy to install, economical, and environmentally friendly. In Kubu Raya Regency, the growth of home industries producing paving blocks has increased rapidly to meet local demand. However, many of these industries have not yet met the quality standards set in SNI 03-0691-1996. This study aims to evaluate the quality of paving blocks produced by five home industries in the region by conducting compressive strength and water absorption tests. The method used was an experimental quantitative approach, in which each industry was tested with 20 paving block samples measuring 21×10×6 cm. The compressive strength test results showed that PT Arsa Beton and CV Kalimantan Beton met the quality classification A (≥35 MPa), while Paving Pontianak and Rivacon fell into quality B (≥17 MPa), and Ampera Loster only met quality D (≥8.5 MPa). The water absorption test also showed similar results, where PT Arsa Beton and Rivacon met quality A requirements (≤3%), while Ampera Loster was classified as quality D (≤10%). Overall, home industries that used press machines were able to produce paving blocks with higher quality compared to manual production. This research provides recommendations for quality improvement for small-scale industries to become more competitive and compliant with national standards. Keywords: Paving Block, Home Industry, Compressive Strength, Water Absorption, Quality Standard